PENGARUH BIAYA PRODUKSI TERHADAP HASIL PRODUKSI PADA HOME INDUSTRI SAMBEL PECEL DI KOTA MADIUN - Iin Purwanti (Universitas PGRI Madiun, 2014)
This study aims to determine the production cost home industry of sambel pecel, to determine sambel pecel production in Madiun, and to know is there any effect on the cost of production yield at home industry of sambel pecel Madiun. The samples in this study using a sample that is saturated all home industries of sambel pecel in the city of Madiun, amounting to 34 Home industry of pecel. Data collection using interviews and documentation. In analyzing the data used linear regression analysis to test the hypothesis put forward in this study.The results showed that the cost of production has an influence as well as a positive relationship to yield at Home industry of sambel pecel in the city of Madiun. It is derived from the value rhit rtab 0.339 0.982 whereas on the other hand Sighit value of 0.00 and Sigpro ≤ 0.05. This means that rhit ≥ rtab (0.982 ≥ 0.339) or Sighit ≤Sigpro (0.00 ≤ 0.05), which suggested a rejection of H0 means that production costs have a relationship with industrial production at home industry of sambel pecel at Madiun city. It also obtained the Fhit, while the value of 875.064 Ftab 4,149 value on the other hand is known Sighit 0.00 and Sigpro 0.05. This means that the Fhit ≥ Ftab (4.149≥875.064) ≤ Sighit≤ Sigpro (0,00 ≤ 0,05). Meaning a rejection of H0 which indicates that there is a cost impact of production on industrial production at home industry of sambel pecel at Madiun city. Also obtained regression coefficients (t test) with thit 29.581 ttab 1.693 on the other hand Sighit 0.00 and Sigpro 0.05. This means that the thit ≥ ttab(29.581 ≥ 1.693) or Sighit ≤ Sigpro (0,00 ≤ 0,05). Results R2 of 96.5%. Showed that 96.5% of the variable cost of production is affected production, while the remaining 3.5% is influenced by other factors.